Predicting the Determinants of Nutritional Behaviors among High School Female Students: The Application of Extended Theory of Reasoned Action - Zahra Baji; Ghodratollah Shakerinejad; Masoumeh Tehrani; Farzaneh Jarvandi; Saeedeh Hajinajaf (Journal of Education and Community Health)
Aims: Unhealthy nutrition is the cause of 35% of death due to cancer. Modification of dietary patterns from childhood and beginning adulthood and having good nutritional behaviors is very important to prevent diseases. The aim of this study was to determine the predictive factors of nutritional behaviors based on the extended theory of reasoned action among high school female students. Instrument & Methods: In this cross-sectional descriptive-analytical study, 173 high school female students were selected by simple random sampling method from two girls' government schools in Ahvaz city in academic year 2018-2019. Data were collected using a questionnaire including demographic characteristics, extended theory of reasoned action and nutritional behaviors questions. Data analysis was performed using structural equation modeling and independent t-test, chi square test and Pearson correlation coefficient in SPSS 23 and AMOS 22 softwares. Findings: The amount of expression of behavioral intention variance was 28% for attitude, 15% for subjective norms, and 49% for self-efficacy and self-efficacy and subjective norms were the most powerful and weakest predictor of behavioral intention respectively. Also 56% of behavioral intention changes and 24% of nutritional behavior changes of students were predicted by this extended model. The fitting indexes of the model showed that the model is goodness. Conclusion: The extended theory of reasoned action with the self-efficacy construct is a suitable theory for predicting nutritional behaviors of female students.